Re-Opening of Classes, Philippine Setting: The State of Mental Health and Adaptation - Cyril B. Romero (The Indonesian Institute of Science and Technology Research, 2022)
The rapid transmission of COVID-19 throughout the world has had health, social, psychological, economic and, of course, educational consequences. In fact, school closure has been, on a global scale, one of the most widely used measures for helping to maintain social distancing and to decrease infections. This research is an opinion on how schools were opened in the Philippines and their impact on mental health and adaptation. This research is an opinion study that uses several lieteratures to corroborate opinions. I believe that what we are suffering now is just temporary, sooner we will be healed. Through our prayers, and the observance of health protocols, coupled with the support of the government, our country, the Philippines and Indonesia too, and the whole world will recover from this unpleasant and dreadful effect of pandemic. Our country Philippines is very hopeful that the word pandemic will be changed to endemic.